Mood, cognitive function and quality of life improvements in middle aged women following supplementation with Polygonum minus extract - Hanis Mastura Yahya,; Suzana Shahar,; Siti Nur Arina Ismail,; Ainor Farahin Aziz,; Normah Che Din,; Bibi Nabihah Abdul Hakim, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Polygonum minus is a plant rich in flavonoids and antioxidants beneficial for reducing oxidative stress and lipid peroxidation in neuronal membranes. This randomized, double-blind, placebo-controlled study evaluated the potential benefits of P. minus extract (LineMinusTM) towards improving cognitive function, mood status and quality of life. Thirty five middle-aged women (35-55 years old) were randomized into intervention (n=17) and control group (n=18). Two capsules of P. minus (250 mg) or placebo (100 mg maltodextrin) each were taken once daily for six weeks. Cognitive tests, mood and anthropometric measurements were measured at baseline, week 3 and week 6, whilst biomarkers were measured at baseline and week 6. Parameters related to mood and quality of life including energy/fatigue, social functioning and general health significantly improved from baseline to week 6 in the intervention group (p<0.05). Mean score for cognitive tests (i.e. digit span, comprehensive trail making test (CTMT) and three domains of CNS vital sign (CNSVS)] improved significantly in both intervention and control groups (p<0.05). There was a significant decrease of mean uric acid, estimated glomerular filtration rate (eGFR), total cholesterol and glycated hemoglobin (HbA1C) in the intervention group from baseline to week 6. P. minus supplementation has the potential to improve mood and quality of life and no adverse effects were reported by the participants after 6 weeks supplementation.